Anti-infertility Effects of Zinc (Zn) Supplements on the Spermatozoa Quality of Rats (Rattus norvegicus L.) Exposed to Cigarette Smoke - Wa Ode Harlis; Rasna Rostika Rasna; Adi Karya; Resman Resman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Cigarette smoke contains nicotine compounds (C10H14N2), tar and carbon monoxide (CO), which cause inhibition of Leydig cells, damage to seminiferous tubules and damage to spermatozoa cells. The aim of this study was to determine the anti-infertility effect of Zinc supplements on the quality of Wistar rat (Rattus norvegicus L.) spermatozoa exposed to cigarette smoke. This research is an experimental study consisting of 4 treatments with 3 replications: Control (drinking water), P1 (14 mg/g BW), P2 (28 mg/g BW), and P3 (42 mg/g BW) Zinc. Exposure to cigarette smoke was carried out twice a day for 14 days in all treatments, and zinc was given for 14 days in treatments P1, P2 and P3. On the 29th day, mice were sacrificed by anesthesia using chloroform and dissected to observe the quality of spermatozoa with parameters of motility, viability and morphology. Data were analyzed using ANOVA (Analysis of Varience) and the BNT test with a 95% confidence level. The results showed that Zinc supplementation in treatments P1 and P2 significantly improved spermatozoa quality, whereas in P3 it decreased significantly. The conclusion of this study is that Zinc (Zn) supplements at a dose of 14 mg/g BW (P1) and a dose of 28 mg/g BW (P2) have an anti-infertility effect by improving the quality of rat spermatozoa that have been exposed to cigarette smoke. The results of this research can be important information for improving male reproduction due to exposure to free radicals from cigarette smoke.